Prevention of sexual harassment in Organisations: Evidence from Sri Lanka. - Adikaram, Arosha S.; Kailasapathy, Pavithra (My University, 2021)
The aim of this paper is to present a framework that elucidates what Human Resource Professionals (HRPs) can do in practice to prevent sexual harassment in Sri Lankan companies through the experiences and successful practices of over 30 Sri Lankan companies. Using a qualitative approach, we interviewed 35 human resource professionals from 30 organisations in Sri Lanka. The Theory of Planned Behaviour is used as the theoretical lens of the study. Findings indicate numerous primary and auxiliary strategies and practices organisations use to prevent the occurrence of sexual harassment. The primary strategies include policies and procedures, effective complaint handling and communication and training. Auxiliary strategies include culture of respect, top management who lead by example, recruitment of the right people, protective measures and knowledgeable and capable HRPs. The findings move beyond the commonly discussed preventive strategies that are mainly discussed in the Western context and present a more context specific uncommon strategies that can be used in combination to successfully prevent sexual harassment. This framework will further assist in understanding the actual practices companies engage in to prevent sexual harassment and identify the drawbacks in some of the practices as well.
Keywords: sexual harassment; prevention; policies; communication; training